Answer:
A
Step-by-step explanation:
Given the 2 equations
4x + 5y = - 12 → (1)
- 2x + 3y = - 16 → (2)
Eliminate the x- term by multiplying (2) by 2 and adding the result to (1)
- 4x + 6y = - 32 → (3)
Add (1) and (3) term by term
11y = - 44 ( divide both sides by 11 )
y = - 4
Answer:
f(g(-7))
Step-by-step explanation:
You divide 1 by 4.76 and you get 0.21 as your main answer
Answer: no because you get a decimal
Step-by-step explanation:
Answer:
The coefficient of the quadratic term ,a,determines how wide or narrow the graphs are, and
weather the graph turns upward or downward
Step-by-step explanation:
this is your answer